Fluid mechanics for chemical engineers : - Wilkes, James O. (Prentice Hall Professional Technical Reference, 2006)
The Chemical Engineer's Practical Guide to Contemporary Fluid Mechanics Since most chemical processing applications are conducted either partially or totally in the fluid phase, chemical engineers need a strong understanding of fluid mechanics. Such knowledge is especially valuable for solving problems in the biochemical, chemical, energy, fermentation, materials, mining, petroleum, pharmaceuticals, polymer, and waste-processing industries. Fluid Mechanics for Chemical Engineers, Second Edition, with Microfluidics and CFD, systematically introduces fluid mechanics from the perspective of the chemical engineer who must understand actual physical behavior and solve real-world problems. Building on a first edition that earned Choice Magazine's Outstanding Academic Title award, this edition has been thoroughly updated to reflect the field's latest advances. This second edition contains extensive new coverage of both microfluidics and computational fluid dynamics, systematically demonstrating CFD through detailed examples using FlowLab and COMSOL Multiphysics.The chapter on turbulence has been extensively revised to address more complex and realistic challenges, including turbulent mixing and recirculating flows. Part I offers a clear, succinct, easy-to-follow introduction to macroscopic fluid mechanics, including physical properties; hydrostatics; basic rate laws for mass, energy, and momentum; and the fundamental principles of flow through pumps, pipes, and other equipment.Part II turns to microscopic fluid mechanics, which covers *Differential equations of fluid mechanics *Viscous-flow problems, some including polymer processing *Laplace's equation, irrotational, and porous-media flows *Nearly unidirectional flows, from boundary layers to lubrication, calendering, and thin-film applications *Turbulent flows, showing how the k/e method extends conventional mixing-length theory *Bubble motion, two-phase flow, and fluidization *Non-Newtonian fluids, including inelastic and viscoelastic fluids *Microfluidics and electrokinetic flow effects including electroosmosis, electrophoresis, streaming potentials, and electroosmotic switching *Computational fluid mechanics with FlowLab and COMSOL Multiphysics Fluid Mechanics for Chemical Engineers, Second Edition, with Microfluidics and CFD, includes 83 completely worked practical examples, several of which involve FlowLab and COMSOL Multiphysics. There are also 330 end-of-chapter problems of varying complexity, including several from the University of Cambridge chemical engineering examinations. The author covers all the material needed for the fluid mechanics portion of the Professional Engineer's examination.The author's Web site, www.engin.umich.edu/~fmche/, provides additional notes on individual chapters, problem-solving tips, errata, and more.